2006
DOI: 10.1242/jeb.02279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate and substantial hypoxia on erythropoietin levels in rainbow trout kidney and spleen

Abstract: SUMMARY Erythropoietin (EPO) is a glycoprotein hormone that regulates the proliferation and differentiation of erythroid progenitor cells in mammals. Although EPO has been identified in fish, the specific function and effects of hypoxia have not been investigated previously. In this study, we have demonstrated a relationship between increases in renal EPO levels and decreases in spleen EPO levels and spleen-somatic index (SSI), with increases in haemoglobin (Hb) concentration in the blood during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 11 publications
2
59
1
2
Order By: Relevance
“…Although the most likely source of this short-term increase in Hb is a release of erythrocytes from the spleen, erythropoietin (EPO) may have also stimulated the formation of new red blood cells (Gallaugher and Farrell, 1998;Nikinmaa and Rees, 2005). Indeed, injection of EPO into goldfish stimulates red blood cell production (Taglialatela and Della Corte, 1997) and, as observed in this study, hypoxia has now been shown to induce EPO production in several fish species (Lai et al, 2006;Yaqoob et al, 2009;Dangre et al, 2010). Interestingly, mammalian studies have shown that leptin can also enhance the proliferation of hematopoietic stem cells and stimulate the production of erythrocytes (Bennett et al, 1996).…”
Section: Discussionmentioning
confidence: 53%
“…Although the most likely source of this short-term increase in Hb is a release of erythrocytes from the spleen, erythropoietin (EPO) may have also stimulated the formation of new red blood cells (Gallaugher and Farrell, 1998;Nikinmaa and Rees, 2005). Indeed, injection of EPO into goldfish stimulates red blood cell production (Taglialatela and Della Corte, 1997) and, as observed in this study, hypoxia has now been shown to induce EPO production in several fish species (Lai et al, 2006;Yaqoob et al, 2009;Dangre et al, 2010). Interestingly, mammalian studies have shown that leptin can also enhance the proliferation of hematopoietic stem cells and stimulate the production of erythrocytes (Bennett et al, 1996).…”
Section: Discussionmentioning
confidence: 53%
“…Increasing the number of circulating RBCs in response to hypoxia to enhance O 2 transport, via erythropoiesis or splenic release, is a strategy used by many fishes (e.g. Tetens and Lykkeboe, 1981;Murad et al, 1990;Soldatov, 1996;Lai et al, 2006), but there are exceptions (e.g. McLeod et al, 1978;Routley et al, 2002).…”
Section: Research Articlementioning
confidence: 99%
“…For example, elevated [Hb] enhances the blood O 2 carrying capacity (Lai et al, 2006;Petersen and Gamperl, 2011;Wells et al, 1989). Similarly, increased Hb-O 2 affinities are commonly reported to improve the O 2 -uptake capacity of Hb during environmental hypoxia (Weber et al, 1976;Wood and Johansen, 1972).…”
Section: Is There Evidence Of Aerobic Adjustments Improving Hypoxia Tmentioning
confidence: 99%